A szervezeti biztonság és a munkahelyi stressz kapcsolata - Lazányi Kornélia (Taylor : gazdálkodás- és szervezéstudományi folyóirat, 2016)
For ages, the literature of organisational safety and security has focused exclusively on threats stemming from the surrounding of the organisation, and has been targeted on the “bulletproof” protection of the organisation as a plant, a technical or informatical architecture and not as a complex socio-technical entity. With the spread of the holistic organisational approaches the internal focus – emphasising the role of individuals and groups within the organisation – of the organisational security has gained ground; however the aim at 100% security still remained. Even the newest concept of organisational security – the security culture – endeavours to eradicate safety threats from the life of organisations. Present paper – on the basis of international literature on stress and its effects – intends to point out that this approach of organisational security fails to take into consideration an important factor, namely the lack of stress and hence abundance of motivation, arousal intent and energy on the organisational actors’ side.